Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/bi0492152
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Active ScFv to G-Protein-Coupled Receptor CCR5 Using Surface Antigen-Mimicking Peptides

Abstract: This study describes the use of cyclic peptides for use in the selection of single-chain (ScFv) antibodies specific for the HIV-1 coreceptor CCR5, a representative G-protein-coupled receptor (GPCR). A tandem ligation strategy was developed for preparing biotinylated cyclic peptides, first through an orthogonal end-to-end ligation and then a chemoselective ligation with functionalized biotin. Cyclic peptides mimicking the extracellular loops of CCR5 and their unconstrained counterparts were then used for soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Having shown that the linear synthetic peptide CCR5 89-102 is poorly immunogenic, we turned our attention to its cyclic form and to the FHV Epitope Presentation System. Analogous to our results, a recent report has shown that it is possible to select anti-CCR5 single-chain variable fragments from a phage display antibody library and that only those selected by binding to cyclic constrained peptides inhibited CCR5-mediated (but not CXCR4-mediated) HIV infection (40).…”
Section: Discussionsupporting
confidence: 87%
“…Having shown that the linear synthetic peptide CCR5 89-102 is poorly immunogenic, we turned our attention to its cyclic form and to the FHV Epitope Presentation System. Analogous to our results, a recent report has shown that it is possible to select anti-CCR5 single-chain variable fragments from a phage display antibody library and that only those selected by binding to cyclic constrained peptides inhibited CCR5-mediated (but not CXCR4-mediated) HIV infection (40).…”
Section: Discussionsupporting
confidence: 87%
“…Cyclic peptides have also been successful in the isolation of scFv phage antibodies targeted to the extracellular loops of CCR5. 53 Chemical Linkage of Peptides onto Scaffolds (CLiPS) technology has also been used successful to generate functional antibodies to CXCR7.…”
Section: Immunogen Formats Used For Gpcrsmentioning
confidence: 99%
“…In addition, the second loop is mostly responsible for the binding of the endogenous chemokine peptides (42). Moreover, very recently a high level of immunogenicity has been found to both the N terminus and the first cysteine loop (49). Taken together, these findings suggest that the external domains of CCR5 are not clearly independent.…”
mentioning
confidence: 99%